Description of the Satisfaction Level of Training Participants on Service In Batam Health National Training Centre, Indonesia - Supriyono; Sriyatun (International Journal of Science and Society, 2020)
This study aims to describe the level of satisfaction of trainees towards services in Batam health training using the customer satisfaction index (CSI) and the community satisfaction index (IKM). The population in this study were all trainees who used services in Batam health training. The sample in this study was saturated, where all participants were taken as samples, with 374 respondents. Data collection methods used were questionnaires or questionnaires. The results showed that the customer satisfaction index reached 0.94 was very satisfied, with the highest IKP in learning facilities services and the desire of respondents to recommend the Batam Health Agency to friends and colleagues reached 0.96% and the lowest service level of teaching and learning activities reached 0.88%. While the index of community satisfaction reached a value of 70.21 B, the predicate of the performance of service units in the Batam Health Agency is good. Overall the trainees felt very satisfied.